A study on the Effect of Draught and Dust Amount on the Prevalence of Tuberculosis in Zabol City - Mohammad Malakootian; Mostafa Mish MastNehi (Kerman University of Medical Sciences, 2018)
A study on the Effect of Draught and Dust Amount on the Prevalence of Tuberculosis in Zabol City   Malakootian Mohammad1, Mostafa Mish MastNehi2*   1. Professor, Research Center of Environment Health Engineering, Kerman University of Medical Sciences, Kerman, Iran. 2. MSc, Zabol University of Medical Sciences, Zabol, Iran. *Correspondence: St. Shahid Bagheri, Jahad Square, Deputy in University of Medical Sciences, Zabol. Tel: 00985432230515                                               Email: Asnehi0@gmail.com Abstract: Background & Objectives: Tuberculosis is a chronic bacterial disease that can be transmitted from the affected persons to others through air when the airway and lung drops of patients are released in the air and inhalled by healthy ones. This disease has a high prevalence in Zabol/ Iran due to the drought, rainfall status, high temperature, severe storms and dusty condition in this region. Methods: This descriptive-analytical research was conducted from June 2005 to June 2015 using weather data and the 10-year statistics of tuberculosis patients in Zabol city, of whom 62 patients had been treated. A researcher-made questionnaire was used to identify the factors affecting the disease. Data analysis was done through SPSS22 software and using Pearson correlation and regression analyses. Results: Climatological data showed increasing rate of wind speed over the past ten years. There was a negative correlation between the prevalence of tuberculosis and mean of annual rainfall during the ten years (P≤0.014). The results of regression test showed that wind speed had been very effective in the prevalence of tuberculosis (P = 0.711). Conclusion: To control tuberculosis, regular periodic screening, continuous education and more serious plans for providing specialized care and services are recommended. Meanwhile, appropriate measures including mulching and increasing plant coverage of the region should be taken to control dust.   Keywords: Tuberculosis, Drought, Dust, Weather station, Zabol city   Citation: Malakootian M, Mish MastNehi M. A study on the Effect of Draught and Dust Amount on the Prevalence of Tuberculosis in Zabol City. Journal of Health Based Research 2018; 4(1): 1-11.